2017
DOI: 10.14800/ics.1506
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin in inflammation and immunity in social insects

Abstract: Social insects, such as the honey bee and ants, form vast colonies that are only rivalled by human settlements. Living in dense, often stationary groups is prone to increase disease transmission. Yet, social insect queens and certain worker types can lead lengthy lives compared to the life span of most solitary insects. Social insects appear to have modified insulin/insulin like signaling pathway that regulates insect life history. This modification results in extremely elevated levels of the multifunctional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…The humoral response includes production of various compounds, such as eicosanoids, phenoloxidases, proteinases, proteinase inhibitors and a wide selection of antimicrobial peptides and proteins (Jiang, 2008;Beckage, 2008). The list of the protective compounds also includes Vgs, whose involvement in insect defense systems has recently been described in several insect species (Havukainen et al, 2013;Singh et al, 2013;Salmela et al, 2015;Salmela and Sundstrom, 2017;Park et al, 2018). We have found in this study that in the firebug P. apterus, Vg is probably also involved in the defense reaction against the entomopathogenic nematode S. carpocapsae and, partially, against the fungus I. fumosorosea.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The humoral response includes production of various compounds, such as eicosanoids, phenoloxidases, proteinases, proteinase inhibitors and a wide selection of antimicrobial peptides and proteins (Jiang, 2008;Beckage, 2008). The list of the protective compounds also includes Vgs, whose involvement in insect defense systems has recently been described in several insect species (Havukainen et al, 2013;Singh et al, 2013;Salmela et al, 2015;Salmela and Sundstrom, 2017;Park et al, 2018). We have found in this study that in the firebug P. apterus, Vg is probably also involved in the defense reaction against the entomopathogenic nematode S. carpocapsae and, partially, against the fungus I. fumosorosea.…”
Section: Discussionsupporting
confidence: 54%
“…However, low levels of Vgs have been identified in males of several insect species, including the firebug Pyrrhocoris apterus (Nemec et al, 1993). Several recent studies suggested that Vgs play an important role not only in reproduction but also in other aspects of insect biology, such as the caste differentiation process in social insects, wound healing, protection against oxidative stress, immunity and life span regulation (Havukainen et al, 2013;Singh et al, 2013;Salmela et al, 2015;Salmela and Sundstrom, 2017;Park et al, 2018). Studies in the silkworm and honeybee reported strong antibacterial activity of Vg against gram-positive and gram-negative bacteria (Singh et al, 2013), showing that Vg bound to bacterial cells and destroyed them.…”
Section: Introductionmentioning
confidence: 99%
“…In other social insects, this linkage between JH, Vg and behaviour is similar [23,3840], absent [41] or reversed [4244]. Moreover, Vg underwent multiple duplications in ants with different orthologs taking over specific functions in the regulation of fertility and behaviour [31,4549]. In honey bees, the foraging gene is highly expressed in the optical lobes and mushroom bodies of forager’ brains [50,51], causing an elevated sucrose responsiveness and the onset of foraging behaviour [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…This yolk precursor is known to have antimicrobial activity and plays a role in immunity across a variety of taxonomical groups (e.g. [32,[40][41][42]47,[49][50][51]). Our results indicate that E1 embryos, which probably have the highest concentration of maternally contributed vitellogenins before becoming metabolized during embryogenesis, reduced conidia germination by approximately 10% (figure 4b).…”
Section: Discussionmentioning
confidence: 99%